Enhancement of Tumor Homing by Chemotherapy‐Loaded Nanoparticles. Issue 45 (7th October 2018) - Ponzoni, Mirco; Curnis, Flavio; Brignole, Chiara; Bruno, Silvia; Guarnieri, Daniela; Sitia, Leopoldo; Marotta, Roberto; Sacchi, Angelina; Bauckneht, Matteo; Buschiazzo, Ambra; Rossi, Andrea; Di Paolo, Daniela; et al.
Abstract: Targeted delivery of anticancer drugs with nanocarriers can reduce side effects and ameliorate therapeutic efficacy. However, poorly perfused and dysfunctional tumor vessels limit the transport of the payload into solid tumors. The use of tumor‐penetrating nanocarriers might enhance tumor uptake and antitumor effects. A peptide containing a tissue‐penetrating (TP) consensus motif, capable of recognizing neuropilin‐1, is here fused to a neuroblastoma‐targeting peptide (pep) previously developed. Neuroblastoma cell lines and cells derived from both xenografts and high‐risk neuroblastoma patients show overexpression of neuropilin‐1. In vitro studies reveal that TP–pep binds cell lines and cells derived from neuroblastoma patients more efficiently than pep. TP–pep, after coupling to doxorubicin‐containing stealth liposomes (TP–pep–SL[doxorubicin]), enhances their uptake by cells and cytotoxic effects in vitro, while increasing tumor‐binding capability and homing in vivo. TP–pep–SL[doxorubicin] treatment enhances the Evans Blue dye accumulation in tumors but not in nontumor tissues, pointing to selective increase of vascular permeability in tumor tissues. Compared to pep–SL[doxorubicin], TP–pep–SL[doxorubicin] shows an increased antineuroblastoma activity in three neuroblastoma animal models mimicking the growth of neuroblastoma in humans. The enhancement of drug penetration in tumors by TP–pep‐targeted nanoparticles may represent an innovative strategy for neuroblastoma. Abstract : A neuroblastoma‐recognizing peptide is modified by adding a consensus motif as a mediator of tissue penetration. A chemotherapy‐loaded nanocarrier, functionalized with this peptide, dramatically increases tumor uptake, penetration, and diffusion of the encapsulated drug into tumors. This leads to enhanced antitumor effects in three mouse models of human neuroblastoma, paving the way to clinical translation.